Speed and position control of autonomous mobile robot on variable trajectory depending on its curvature - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2009)
This paper presents design of autonomous mobile robot MBR-01 for speed and position control on variable trajectory depending on trajectory curvature. MBR-01 can communicate reciprocally with host computer using RF data transceiver. Road data image is captured by CCD camera mounted on vehicle and transferred to host computer using RF data link unit. Applying image processing on trajectory, reference speed has been produced depending on curvature of trajectory. Reference speed is applied to fuzzy controller unit and output is sent to vehicle by wireless transmitter unit. Received control signal by vehicle is transferred to DC motor drive system with Pulse Width Modulation techniques. Position control is realized by microprocessor-based units mounted on vehicle. Equipped 7 optical sensors detect trajectory deviation and wheel angle of vehicle for track detection and wheel angle detector
Keywords: Autonomous mobile robot; Fuzzy edge detection; position control; Speed control; FUZZY; TRACKING; DESIGN